Biosemiotics: Communication and Causation (Information included) - Juan Ramon Álvarez (tripleC: Communication, Capitalism & Critique)
Pretensions of Biosemiotics as a unified approach to biological information are critically scrutinized within the study of different projects of semiotisation of nature and naturalization ot cultural processes. Main textual references and arguments are presented and critically pondered. Biosemiotics is here presented as an analytical method to study communication as founded in causality.